Impact of Infrastructure Development and Poverty on Human Development Index in East Java (2018-2022) Using GWPR - Muhammad Zainul Haq; Siti Komariyah; Lilis Yuliati (International Journal of Economics, Commerce, and Management, 2025)
In the last ten years, Indonesia has been carrying out massive infrastructure development. The goal is to facilitate community mobility which has an impact on economic growth. Infrastructure development also aims to increase the Human Development Index even though it does not directly affect it. One of the provinces that contributed to infrastructure development was East Java, with the Human Development Index during the 2018-2022 period increasing and tending to stagnate. For this reason, the purpose of this study is to identify the influence of infrastructure development on the Human Development Index, including identifying the influence of poverty on the Human Development Index. The research methodology used is quantitative with a Geographically Weighted Panel Regression (GWPR) approach that allows to comprehensively identify the Regional Development Index in East Java. The results obtained were that the variables of Infrastructure Development with the dimensions of Road Length (6,172) and Number of Schools (2,686) had an impact on the Human Development Index in East Java. Meanwhile, the poverty variable (-6,139) has no effect on the Human Development Index (HDI). However, simultaneously the variables of Infrastructure Development and Poverty affect the National Development Index (HDI) with a calculation of 64.42 > 2.4202.